2016
DOI: 10.1126/scisignal.aaf5642
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic DNA methylation regulates neuronal intrinsic membrane excitability

Abstract: Epigenetic modifications, such as DNA cytosine methylation, contribute to the mechanisms underlying learning and memory by coordinating adaptive gene expression and neuronal plasticity. Transcription-dependent plasticity regulated by DNA methylation includes synaptic plasticity and homeostatic synaptic scaling. Memory-related plasticity also includes alterations in intrinsic membrane excitability mediated by changes in the abundance or activity of ion channels in the plasma membrane, which sets the threshold f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 120 publications
(212 reference statements)
1
42
0
1
Order By: Relevance
“…That important function may rely on stable changes at the synapse (but see refs. 62,63 ) or on learning-related transcriptional changes other than those mediated by CREB 64,65 (for the potential utility of hypothesized long-term changes in excitability, see ref. 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…That important function may rely on stable changes at the synapse (but see refs. 62,63 ) or on learning-related transcriptional changes other than those mediated by CREB 64,65 (for the potential utility of hypothesized long-term changes in excitability, see ref. 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is now evidence for epigenetic and transcriptional regulatory processes that control learning-dependent changes, including global changes in cellular excitability (Abel and Klann, 2013; Meadows et al, 2016; Yiu et al, 2014; Zhou et al, 2009). Thus, both cell-wide and synapse-specific processes may be necessary for memory storage (J. Lisman and A. Silva; in preparation).…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Although it is unknown if heavy ethanol drinking in macaques alters firing properties of NAcC MSNs, the shift in transcript variants and the reduction in total KCa2 channel protein suggests that prolonged ethanol intake will increase intrinsic excitability similar to results from rodent models of ethanol self-administration (11) and dependence (13,78). In addition to reduced Kcnn3 gene expression and increased intrinsic excitability, a recent study reported a loss of apamin's ability to increase evoked firing in cultured cortical neurons treated with DNA methyltransferase inhibitors (33). Thus, these data provide support that the increase 20 in SK3_ex1B and SK3_ex4 TV expression through hypermethylation of KCNN3 exon 1A is an underlying mechanism driving these functional and behavioral adaptations across species and brain regions.…”
Section: Discussionmentioning
confidence: 90%
“…DNA methylation (DNAm) is an epigenetic mark that can contribute to modulation of gene expression by modifying the compaction status of the chromatin. Alterations in DNA methylation are reported in heavy drinking monkeys and rodents (30)(31)(32), and a recent study demonstrated that knockdown of DNA methyltransferases reduced Kcnn3 expression and increased intrinsic excitability of cultured cortical neurons (33). Thus, we measured DNAm levels at a differentially methylated region (DMR) in exon 1 that coincides with a cross-species regulatory region within the KCNN3 promoter.…”
Section: Introductionmentioning
confidence: 99%